Putting farmers at the centre of climate information services - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
In pilot trainings in Tanzania, farmers have received climate data together with participatory tools to help them evaluate their options and make on-farm decisions. The approach is now being scaled up in Malawi and Tanzania through training agricultural extension agents and NGO staff to provide climate information and decision-making tools.